Ринок праці Волинської області: статистичне дослідження економічної активності населення - Бегун, Світлана; Черчик, Лариса; Cherchyk, Larysa; Begun, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2019)
Багатовимірне статистичне дослідження ринку праці необхідне для прийняття обґрунтованих управлінських рішень на мікро-, мезо- та макрорівні. Воно включає оцінювання ринкової ситуації щодо зайнятості та безробіття, характеристику тенденцій і пропорцій ринку, визначення ефективності попиту та пропонування робочої сили. У статті представлено результати першого етапу комплексного статистичного аналізу ринку праці Волинської області за 2013-2018 роки, а саме економічної активності населення за віковими категоріями, зайнятого та безробітного населення. Здійснено порівняльний аналіз зміни чисельності економічно активного та економічно неактивного населення Волинської області з аналогічними по Україні, аналіз структурних зрушень в чисельності економічно активного населення за рівнем освіти.
Changes in the economy of Ukraine require solving the problem of forming a competitive labor market. This requires the definition of priority areas for regulation of the labor market and employment at the national and regional levels, which require adequate statistical and information-analytical support. The purpose of the article is to conduct a multidimensional statistical analysis of the labor market of Volyn region for the period 2013-2018. Results. A multidimensional statistical survey of the labor market is needed to make sound management decisions at the micro, meso and macro levels. It involves assessing the market situation for employment and unemployment, characterizing trends and market proportions, determining efficient demand and supply. The article presents the results of the first stage of a comprehensive statistical analysis of the Volyn region's labor market in 2013-2018, namely economic activity of the population by age categories, employed and unemployed population. Comprehensive statistical analysis showed that economic activity indicators were the best in 2016, they had worsened in 2017 and increased slightly in 2018 but did not reach levels in 2016. The level of economic activity of the region's population decreased by 13,7% over five years, the employment rate decreased by 17,1%, the unemployment rate increased by 46,2%. A comparative analysis of trends in the number of economically active and economically inactive population of Volyn region with the same in Ukraine shows that the trends are the same, but the indicators characterizing the region's labor market in 2013-2018 are worse than in Ukraine. Structural changes in the number of economically active population by type of education are insignificant. Conclusions. The level of economic activity of the population of the region in the five years has significant decreased by 13,7%, the employment rate decreased by 17,1%, the unemployment rate increased by 46,2%, which is a negative trend.
Keywords: ринок праці; економічно активне населення; зайняте населення; безробітне населення; labor market; economically active population; employed population; unemployed population